Berjabat Tangan dengan Lawan Jenis - Nurul Huda (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
It has been a common practice among society that shaking hands is a symbol of social relations bounding among people, good business relationships, friendship, kinship and others. But, Islam as a religion that aims to regulate the moslem welfare , has been set severel rules in shaking hands between man and woman. Because Islam anticipates its negative impact such as relationship without the status of "love relation" that will continue in adultery, and so forth, and eventually lead to moral decadence among adolescents. This article intends to review this issue from the standpoint of understanding of the verses and hadiths of the Prophet.